Forage Rye Improvement in the Southern United States: A Review. Issue 1 (1st January 2013) - Newell, Mark A.; Butler, Twain J.
Abstract : Rye ( Secale cereale L.) is an important crop worldwide for grain and forage production. Stocker cattle ( Bos spp.) production in the southern United States relies on rye for forage from autumn to spring when warm‐season perennials remain dormant. Because rye has high‐stress tolerance with respect to both soil and environment, it fills a particular niche that spans the winter months for the region. Rye forage yield has not improved over time, due in part to limited breeding effort. Many of the cultivars currently grown in the region were released as early as the 1950s. Similar to other forage crops, gains in forage yield have been small or nonexistent; therefore, an evaluation of the crop in relation to past and current breeding strategies could contribute to the future improvement of the crop. The objectives of this manuscript are to review the rye crop in relation to its cropping system, the genetic considerations for rye in relation to breeding, and past and current breeding efforts and selection processes and then to propose breeding methodologies for the improvement of rye with major focus on forage yield. Methods of selection that rely on family performance in multienvironment trials are recommended. With advancements in breeding methods, rye poses a unique opportunity among the forage crops to enable rapid cycling for development of improved cultivars.